2018
DOI: 10.1016/j.ijnss.2018.03.005
|View full text |Cite|
|
Sign up to set email alerts
|

Supporting nurse practitioner education: Preceptorship recruitment and retention

Abstract: Objectives Clinical experience is an essential component of nurse practitioner (NP) education that relies heavily on preceptors. Recruitment and retention of preceptors is challenging due to many variables that can affect NP education and practice. We surveyed Canadian NP programs to understand their preceptorship structures, how they support preceptorship, and to identify gaps and challenges to recruitment and retention of preceptors. Methods An 18-item survey, develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 12 publications
0
9
0
2
Order By: Relevance
“…Nesse tópico, sete artigos foram incluídos, pois abordaram as diferentes formas de treinamento ou apoio para preceptores. As estratégias variaram de formato, sugerindo a falta de padrões estabelecidos para a formação dos preceptores (Bengtsson & Carlson, 2015a;Bengtsson & Carlson, 2015b;Bolt, Baransk, & Bell, 2016.;Correa et al, 2015;Cox, Cheon, Crooks, & Lee 2017;Staples & Sangster-Gormley, 2018), conforme observa-se no Quadro 4.…”
Section: Estratégias Utilizadas Para a Formação Do Preceptorunclassified
See 1 more Smart Citation
“…Nesse tópico, sete artigos foram incluídos, pois abordaram as diferentes formas de treinamento ou apoio para preceptores. As estratégias variaram de formato, sugerindo a falta de padrões estabelecidos para a formação dos preceptores (Bengtsson & Carlson, 2015a;Bengtsson & Carlson, 2015b;Bolt, Baransk, & Bell, 2016.;Correa et al, 2015;Cox, Cheon, Crooks, & Lee 2017;Staples & Sangster-Gormley, 2018), conforme observa-se no Quadro 4.…”
Section: Estratégias Utilizadas Para a Formação Do Preceptorunclassified
“…Foram encontradas outras estratégias canadenses (Staples & Sangster-Gormley, 2018), como jantares para preceptores com apresentações educacionais. Alguns programas ofereceram uma orientação formal para os preceptores, que consistiam em breves webinars, recursos online para preceptores, reconhecimento formal de preceptores, acesso à biblioteca da universidade em que o programa de residência está inserido, além de acesso à educação dos alunos com materiais complementares, apreciação e reconhecimento de preceptores em eventos de premiação, e ainda oficinas de preceptores (Staples & Sangster-Gormley, 2018).…”
Section: Estratégias Utilizadas Para a Formação Do Preceptorunclassified
“…This requirement adds on to an already busy clinical routine, resulting in inadequate time for preceptorship training, which hinders the ability to foster a positive learning environment (Chan et al., 2019). The preceptor–preceptee relationship is also affected as preceptors find it hard to find time for their preceptees, hampering their relationship building (Staples & Sangster‐Gormley, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Nurse preceptors also express inadequate support from the nursing management and from their peers, which leads to a sense of vulnerability (Girotto et al., 2019; Whitehead et al., 2016). Preceptors feel abandoned in their role as they do not receive feedback on their supervision and are unclear of the expectations that need to be met (Bos et al., 2015; Staples & Sangster‐Gormley, 2018). They also have increasing workload from the management on top of their role as a preceptor and this overwhelming workload can lead to preceptor ‘burnout’ (Jarnulf et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 ] Studies have shown that the provision of specialized nursing programs enables nursing students to act professionally in a particular population and develop their skills. [ 8 ] Nursing postgraduate courses are designed to meet these changing community and professional needs. In Iran, the nursing postgraduate program has been limited for more than two decades, which includes specialists nurse in medical-surgical nursing, pediatric nursing, community health nursing, and mental health nursing fields.…”
Section: Introductionmentioning
confidence: 99%